Maternal mental health disorders associate with their child's asthma: A register-based study - Eetu P. Kanerva; Minna M. Lukkarinen; Marika H. Leppänen; Bernd K. Pape; Päivi T.K. Rautava; Max R.J. Karukivi (Brain, Behavior, & Immunity - Health)
Background: Maternal perinatal mental health disorders contribute to the development of their child's asthma. We investigated the associations between maternal mental health disorders one year before and three years after childbirth to their child's non-allergic asthma and allergic asthma. Methods: From 310701 children born in Finland from 2001 to 2006 and their 232240 mothers, health care registers were collected. Using the International Classification of Diseases 10th revision, a maternal mental health disorder was defined as any mental or behavioral disorder diagnosis (F00−99) from the one year before and three years after childbirth. The outcome was their child's asthma diagnosis (e.g., J45, J45.0, J45.1, J45.8, J45.9, or J46.0) at 7–12 years divided into allergic (J45.0) and non-allergic (J45.1) asthma. Results: Of the children, 19000 (6.1 %) were diagnosed with asthma and 12953 (5.6 %) of the mothers with a mental health disorder. The child's asthma was associated with a maternal mental health disorder (adjusted odds ratio 1.24; 95 % confidence interval 1.16−1.33), smoking during pregnancy (1.08; 1.03−1.13), asthma history (2.94; 2.82−3.06), the mother having a production vs. higher management/executive occupational role (1.16; 1.10−1.23), or the child being male (1.47; 1.42−1.52), all p < .001. Maternal mental health disorders were associated more with their child's non-allergic asthma (1.37; 1.18−1.60) than allergic asthma (1.17; 1.05−1.30), both p < .001. Conclusions: Maternal mental health disorders perinatally and during the early life of their child were associated with their child's asthma supporting intrauterine and early-life programming on the effects of maternal mental health on their child's respiratory morbidity risk.